Energy Price Reform: Lessons for Policymakers. (18th June 2018) - Coady, David; Parry, Ian W H; Shang, Baoping
Abstract: Following the landmark 2015 Paris Climate Agreement, and given concerns about increasing air pollution in many urban areas and historically high fiscal pressures, the need for energy price reform has never been more urgent. Policymakers around the world need guidance on the appropriate level of energy prices and how to address the practical challenges of implementing reforms. This article reviews the recent literature on efficient fossil fuel prices that reflect supply and environmental costs, as well as the benefits of price reform. We also examine recent experiences around the world to identify the key lessons learned for the design of successful reforms.